A critique of the political economy of the European Central Bank - del Rosal, Mario (Papeles de Europa, 2019)
This paper aims to outline an introductory critique of the European Central Bank’s political economy. For this, we will develop an analysis in several stages. First, we will review the origin, nature and traditional functions of the Central Bank as a nuclear institution of the capitalist mode of production. Secondly, we will review the background, genesis and evolution of the ECB, with the aim of comparing this institution with the traditional figure of the Central Bank described in the previous section. Third, we will describe the fundamental theoretical framework that characterizes the ECB, focusing on three of its essential elements: control of inflation as its single objective, political independence and the explicit prohibition of financing states or taking responsibility of their debt. Fourth, we will compare the ordinary monetary policies of the ECB before and after the outbreak of the current crisis in order to check the qualitative change toward a much more expansive management than the original treaties allowed. Finally we will outline some conclusions according to the results achieved.
Keywords: Political Economy; European Central Bank; Monetary Policy; Quantitative Easing; Crisis